2015
DOI: 10.1002/hbm.22791
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of an fMRI paradigm for emotional processing in a multisite longitudinal study

Abstract: Multisite neuroimaging studies can facilitate the investigation of brain-related changes in many contexts, including patient groups that are relatively rare in the general population. Though multisite studies have characterized the reliability of brain activation during working memory and motor functional magnetic resonance imaging tasks, emotion processing tasks, pertinent to many clinical populations, remain less explored. A traveling participants study was conducted with eight healthy volunteers scanned twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 82 publications
13
64
0
Order By: Relevance
“…As shown in Figure 1, when accounting for differential reliability in right fusiform gyrus and right amygdala, although higher levels of power are achieved with smaller sample sizes in the single-site compared with multisite context, multisite studies achieve acceptable levels of power (0.8) with moderate to large effect sizes (ES 0.5) beginning at sample sizes of 85 subjects for the right fusiform gyrus and 125 subjects for right amygdala. These results accord well with the results reported in our original study analyzing single-session scans from 111 healthy subjects, each drawn from one of the eight scanning sites, which observed robust activation in key emotion processing nodes (e.g., amygdala, inferior frontal gyrus, anterior cingulate cortex, fusiform gyrus) whether using image-based-meta-analysis or mixed effects modeling with site as a covariate (Gee et al, 2015), suggesting task-related effect sizes of 0.5 or higher for maximum activation in these regions.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…As shown in Figure 1, when accounting for differential reliability in right fusiform gyrus and right amygdala, although higher levels of power are achieved with smaller sample sizes in the single-site compared with multisite context, multisite studies achieve acceptable levels of power (0.8) with moderate to large effect sizes (ES 0.5) beginning at sample sizes of 85 subjects for the right fusiform gyrus and 125 subjects for right amygdala. These results accord well with the results reported in our original study analyzing single-session scans from 111 healthy subjects, each drawn from one of the eight scanning sites, which observed robust activation in key emotion processing nodes (e.g., amygdala, inferior frontal gyrus, anterior cingulate cortex, fusiform gyrus) whether using image-based-meta-analysis or mixed effects modeling with site as a covariate (Gee et al, 2015), suggesting task-related effect sizes of 0.5 or higher for maximum activation in these regions.…”
supporting
confidence: 89%
“…We wish to make explicit that in applying generalizability theory, we estimated reliability by calculating generalizability and dependability coefficients for a study design corresponding to the design of the full traveling subject study, thus reflecting the reliability in relative and absolute measurement, respectively, that one can expect when every subject is scanned twice on each of eight different scanners. The corresponding generalizability and dependability coefficients (shown in figure 4 and cited in the abstract in Gee et al, 2015) ranged from 0.0 to 0.9 for maximum activation across multiple task contrasts and regions of interest, but were generally at or above 0.5, as would be expected when each subject's measurement is based on the aggregation of 16 scan sessions. Thus, the coefficients reported apply to the reliability of the measures from the reliability study itself, that is, for task-induced brain activations resulting from analysis of the eight traveling subjects' fMRI data considered in aggregate across their 16 scan sessions.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Because fiction literature allows nursing students (through guided imagery and other literary tools), the group with the additional course comprehended empathy and embraced it better than the control group. flow in various regions central to emotion processing during specific task conditions (Gee, McEwen, Forsyth, Haut, Bearden, Addington, and Cannon, 2015). A study performed by Gee et al (2015) has confirmed the reliability in imaging signals of activation of emotion processing regions in the brain when stimulated by relevant tasks.…”
mentioning
confidence: 73%
“…flow in various regions central to emotion processing during specific task conditions (Gee, McEwen, Forsyth, Haut, Bearden, Addington, and Cannon, 2015). A study performed by Gee et al (2015) has confirmed the reliability in imaging signals of activation of emotion processing regions in the brain when stimulated by relevant tasks. Study/test results are only viable when proven in research using reliable sources and equipment.…”
mentioning
confidence: 73%